Prevention of congenital anomalies - Cornel, M. C (Karger, 2002)
Two to six percent of the newborn babies worldwide, i.e. 3-9 million infants a year, suffer from major congenital anomalies and genetic diseases. However, a lot of this misery could be avoided. Examples like congenital rubella syndrome, now largely controlled by vaccination programs, or the identification of drugs like thalidomide and retinoids causing severe birth defects reveal the importance of research and the benefits of primary prevention in this field. \"Community Genetics\" - well aware of the significance for future generations - dedicates this special issue to the prevention of congenital anomalies. One of the most important challenges discussed is the intake of folic acid to prevent neural tube defects and other congenital anomalies. Besides, the treatment of women with diabetes mellitus and epilepsy before and during pregnancy is considered. Other points deliberated are the past and present stages of preconception care in western as well as in developing countries.
Keywords: vrozené vady; Genetics; genetika, lékařská genetika; Congenital Abnormalities; genetika; DĚDIČNÉ NEMOCI